FREQUENCY OF HEART DISEASES IN DOGS AT THE SMALL ANIMAL CLINIC OF THE FACULTY OF VETERINARY MEDICINE, SAN MARCOS UNIVERSITY DURING THE 2007-2009 PERIOD - Calderón O., Karla (2014)
Clinical records from all patients attended in the Small Animal Clinic of the Faculty of Veterinary Medicine, San Marcos University during the period 2007-2009 were revised with the aim of obtaining statistical information about heart diseases in canines. Out of 13 035 clinical records, 260 cases were diagnosed with heart diseases. The chronic atrioventricular valve disease was the most frequent anomaly (71.9% of total heart diseases). Male had a higher risk for heart disease than females (OR = 1.3). The age groups of 9 to 12 and more than 12 years old had also higher risk than the ones younger than 1 year old (OR = 27.9 and 75.9 respectively) and dogs with equal or lower body weight of 10 kg had the highest risk for heart disease (OR = 2.7). Moreover, the Pekingese breed showed greater predisposition to suffer from heart diseases (18.0% of total heart diseases).